2019
DOI: 10.7150/ijbs.23802
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of CSMD1 targeted by microRNA-10b drives gastric cancer progression through the NF-κB pathway

Abstract: Aim:This study aimed to investigate the oncogenic activity of microRNA-10b by targeting CUB and sushi multiple domains protein 1 (CSMD1) in human gastric cancer (GC) and the underlying mechanisms. Methods: The expression of CSMD1 in human GC tissues was evaluated by real-time reverse transcription polymerase chain reaction (RT-PCR), immunoblotting, and immunohistochemical analysis. The expressive abundance of microRNA-10b was detected by stem-loop RT-PCR. Molecular and cellular techniques, including lentiviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…CSMD1 has been characterised, using a range of in vivo and in vitro approaches, and is implicated in various processes, such as testicular development, complement regulation, schizophrenia and in cancer progression [ 9 , 10 , 11 , 12 , 13 ]. In relation to cancer, CSMD1 has been identified as a tumour suppressor with previous studies identifying the chromosome location 8p23 as an area deleted in various cancers, such as breast, head and neck and colorectal [ 1 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Furthermore CSMD1 deletion has also been linked to poor prognosis in patients with late stage breast cancer [ 12 , 17 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…CSMD1 has been characterised, using a range of in vivo and in vitro approaches, and is implicated in various processes, such as testicular development, complement regulation, schizophrenia and in cancer progression [ 9 , 10 , 11 , 12 , 13 ]. In relation to cancer, CSMD1 has been identified as a tumour suppressor with previous studies identifying the chromosome location 8p23 as an area deleted in various cancers, such as breast, head and neck and colorectal [ 1 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Furthermore CSMD1 deletion has also been linked to poor prognosis in patients with late stage breast cancer [ 12 , 17 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…These studies show that pregnant mice have increased ductal growth when Csmd1 is knocked out and in-vitro ductal studies identify more rapid cell growth and duct formation in CSMD1 KO cells [ 11 , 22 ]. These studies, along with further characterisation studies of CSMD1, have identified that the deletion of CSMD1 causes increased cell invasion, motility and proliferation [ 14 , 15 , 22 , 23 ]. These studies therefore suggest a potential role for CSMD1 in the regulation of epithelial mesenchymal transition (EMT).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They also affect the pathogenesis of various cancer types by functioning as oncogenes or tumor suppressor genes [8,9,10,11]. More recently, accumulating reports suggest that miRNAs are associated the various forms of tumorigenesis including lung cancer [12,13,14], prostate cancer [15,16], gastric cancer [17,18], and liver cancer [19,20]. Therefore, characterization of the correlations between miRNAs and their target genes in cancer cells may have a substantial diagnostic, prognostic, and therapeutic value.…”
Section: Introductionmentioning
confidence: 99%